Study on Compact UWB Microstrip Antenna with Quadruple Band-Notched Characteristics for Short Distance Wireless Telecommunication Applications - Rayavaram, Kalyan (New Approaches in Engineering Research Vol. 9, 2021)
In this paper the design and simulation of a compact ultra-wideband (UWB) microstrip antenna with quadruple band-notched characteristics for short distance wireless telecommunication applications were explored. There are various methods which are helpful for introducing a notch in UWB antenna. The most commonly used technique is by adding different slots on the radiating material or in the ground plane or also on the feed line. The design process of the antenna is carried on FR4 substrate with dielectric constant 4.4, loss tangent 0.02, thickness of 0.8mm and the size of the proposed antenna is 30×20 mm2. The rectangular monopole antenna endures a rectangular radiating patch with chamfered bevel slots on the top side, and a defective ground plane on the bottom side of the substrate. To realize single, dual, triple and quadruple band notch characteristics, slot-1 is created on the patch to achieve first notch at 3.5 GHz which eliminates WIMAX signal, slot-2 is created on the patch to achieve second notch at 4.6 GHz which eliminates INSAT signal, slot-3 is created on the patch to achieve third notch at 5.5 GHz which eliminates WLAN signal and also fourth notch is created at 9.5GHz which eliminates X band frequency with slot-1 outer length. The proposed antenna is well miniaturized and can be easily integrated with any compact devices. The simulated result shows that proposed antenna gain a good range of UWB from (2.6 GHz to 13.4 GHz).